Prizefighting and civilization : a cultural history of boxing, race, and masculinity in Mexico and Cuba, 1840-1940 - LaFevor, David C. (University of New Mexico Press, 2020)
In Prizefighting and Civilization: A Cultural History of Boxing, Race, and Masculinity in Mexico and Cuba, 1840-1940, historian David C. LaFevor traces the history of pugilism in Mexico and Cuba from its controversial beginnings in the mid-nineteenth century through its exponential rise in popularity during the early twentieth century.